A study on smoking and secondhand smoke exposure among people at high risk of chronic diseases - Fang ZHOU; Qing-Qing JIANG; Tian-Tian WANG; Shi-Yi CAO (Yixue xinzhi zazhi)
Objective To ascertain tobacco use, secondhand smoke exposure, work environ-ment tobacco control, and awareness of tobacco hazards in groups at high-risk of chronic diseases, providing scientific basis for further formulating intervention strategies suitable for tobacco control and health management for this population.Methods A questionnaire survey and physical examinations were used to investigate the tobacco situation of groups at high-risk of chronic diseases in two large en-terprises and institutions. Descriptive data analysis was performed using chi-square test and rank sum test.Results A total of 868 participants were included in the study. The characteristic with the highest detection rate was smoking, accounting for 63.1%. The proportion of men who smoke was significantly higher than that of women, and the difference was statistically significant (χ2=182.630, P